Maternal mental health problems across early childhood and asthma in school children: Findings from a longitudinal Australian population based study - Bahreinian, Selma; Cooklin, Amanda; Kingston, Dawn; Giallo, Rebecca; Kozyrskyj, Anita; Brown, Stephanie (My University, 2015)
There is a growing body of evidence attesting to links between early life exposure to stress and childhood asthma. However, available evidence is largely based on small, genetically high risk samples. The aim of this study was to explore the associations between the course of maternal depressive symptoms across early childhood and childhood asthma in a nationally representative longitudinal cohort study of Australian children. Participants were 4164 children and their biological mothers from the Longitudinal Study of Australian Children. Latent class analysis identified three trajectories of maternal depressive symptoms across four biennial waves from the first postnatal year to when children were 6-7 years: minimal symptoms (74.6%), sub-clinical symptoms (20.8%), and persistent and increasing high symptoms (4.6%). Logistic regression analyses revealed that childhood asthma at age 6-7 years was associated with persistent and increasing high depressive symptoms after accounting for known risk factors including smoking during pregnancy and maternal history of asthma (adjusted OR 2.36, 95% CI 1.61-3.45), p.001). Our findings from a nationally representative sample of Australian children provide empirical support for a relationship between maternal depressive symptoms across the early childhood period and childhood asthma. The burden of disease from childhood asthma may be reduced by strengthening efforts to promote maternal mental health in the early years of parenting.
PLoS One
Keywords: Stress -- Parenting stress; Children -- Early childhood; Child Development -- Physical; Childhood and child development; Child Development; Children; Stress; Physical; Early childhood; Parenting stress; Childhood and child development